Discipline and Attitude as Predictors of Physical Education Achievement among Elementary School Students - Febrianti, Julhiana; Wahyudi, Johan; Irmansyah, Johan; Ramadhani, Africo (Sportify Journal, 2025)
This study was motivated by limited discipline and positive attitudes among some students in physical education learning, including arriving late to the field, not wearing sports uniforms, paying limited attention to teachers, and complaining during physical activities. The study aimed to examine the contributions of discipline and attitude to physical education achievement at SDN 1 Pringgasela Selatan. A quantitative correlational approach with an ex post facto design was employed. The sample consisted of 60 fifth- and sixth-grade students selected through purposive sampling. Discipline and attitude data were collected using questionnaires, while physical education achievement was obtained from report-card scores. Data were analyzed using simple and multiple linear regression. The findings showed that discipline contributed significantly by 17.8%, attitude by 23.3%, and both variables simultaneously by 25.0%. In the multiple regression model, only attitude remained a significant predictor. The study concludes that attitude is the strongest predictor of physical education achievement.